Selection of (Green) Roof Systems: A Sustainability-Based Multi-Criteria Analysis - Paolo Rosasco; Katia Perini (Buildings, 2019)
A wide diffusion of green envelopes in cities can be an opportunity to improve urban environment conditions and reduce negative effects of climate change. The green roof system is a widespread solution adopted all over the world due to the relative simplicity of installation and the large private and social benefits provided. Despite this, some factors hinder the diffusion of the green roof system, not only economic factors (due to the higher installation costs compare to a traditional roof solution), but also technical factors connected to lack of knowledge. The present paper investigates the factors influencing designers in the choice of a building roof systems, comparing a traditional solution and a greening system. The involvement of architects, engineers, and researchers allows the selection of the most important factors. Results of the study identifies their priority, and through a sustainability-based multicriteria analysis, the role played by each one in the decision process. This approach provides interesting hints to identify effective strategies to support a wider diffusion of greening systems for urban resilience.